1999
DOI: 10.1017/s1355770x99000030
|View full text |Cite
|
Sign up to set email alerts
|

Structural adjustment and deforestation in Nicaragua

Abstract: ABSTRACT. This paper investigates the impact of structural adjustment policies on deforestation taking place when the agricultural frontier advances into forest reserves in Nicaragua. A computable general equilibrium model incorporating deforestation by squatters is used for policy simulations. The opportunity cost of migrating to the frontier does not simply depend on wage income opportunity, but also on market prices of basic grain which determine the capacity to consume beyond subsistence food-level given a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A number of empirical studies have focused on the effects on agricultural land expansion and tropical deforestation of structural adjustment policies-deliberate economic reforms aimed at liberalizing agriculture, forestry and other primary-producing sectors. In general, findings across diverse developing economies, such as Bolivia, Brazil, Ghana, Madagascar, Nicaragua and the Philippines, confirm that such economy-wide reforms, especially those affecting the agricultural sector, had a significant impact on the pattern and extent of agricultural land expansion and forest clearing in the tropics (Benhin and Barbier, 2001;Casse et al, 2004;Cattaneo, 2001Cattaneo, , 2005Coxhead et al, 2001;Glomsrød et al, 1999;Pacheco, 2006). The impacts of structural adjustment reforms targeted at the forestry sector of developing countries are more mixed; although there is little evidence of a direct impact on deforestation, increased wood import by other countries, "price booms" and devaluation of exchange rates may increase timber harvesting and forest loss indirectly (Pandey and Wheeler, 2001;Wunder, 2005).…”
Section: Markets Policies and Institutionsmentioning
confidence: 85%
“…A number of empirical studies have focused on the effects on agricultural land expansion and tropical deforestation of structural adjustment policies-deliberate economic reforms aimed at liberalizing agriculture, forestry and other primary-producing sectors. In general, findings across diverse developing economies, such as Bolivia, Brazil, Ghana, Madagascar, Nicaragua and the Philippines, confirm that such economy-wide reforms, especially those affecting the agricultural sector, had a significant impact on the pattern and extent of agricultural land expansion and forest clearing in the tropics (Benhin and Barbier, 2001;Casse et al, 2004;Cattaneo, 2001Cattaneo, , 2005Coxhead et al, 2001;Glomsrød et al, 1999;Pacheco, 2006). The impacts of structural adjustment reforms targeted at the forestry sector of developing countries are more mixed; although there is little evidence of a direct impact on deforestation, increased wood import by other countries, "price booms" and devaluation of exchange rates may increase timber harvesting and forest loss indirectly (Pandey and Wheeler, 2001;Wunder, 2005).…”
Section: Markets Policies and Institutionsmentioning
confidence: 85%
“…Linking such models with ecological processes is potentially very useful because it allows the effects of broad economic factors such as trade, taxes and credit supply to be evaluated with respect to their ecological outcomes (Persson & Munasinghe 1995). Glomsrod, Monge & Vennemo (1998) apply a macroeconomic approach to deforestation in Nicaragua. Their model showed that a policy of reduced government expenditure would initially drive an increase in deforestation, but that this would eventually reduce deforestation because of a decrease in rural poverty levels and intensification of agriculture on previously deforested land.…”
Section: A Taxonomy Of Socio‐economic Modelsmentioning
confidence: 99%
“…Agricultural expansion in Atlantic Nicaragua, particularly cattle ranching, has accelerated following the end of civil war in 1992 (Glomsrød et al 1997;Horgan 1999;Secretaria de Integración Económica Centroamericana 2002). The region includes a number of large, protected natural areas and numerous 1 C small forest patches.…”
Section: Study Sitesmentioning
confidence: 99%
“…In Central America, an increase in living standards during the 1960s, with an associated demand for meat, led to a rapid increase in cattle production that left much of the PaciWc Coast deforested before the 1980s (Flores Rodas 1976). However, following the cessation of regional civil conXicts in the early 1990s, pasture expansion has become increasingly apparent on the Atlantic Coast, frequently occurring in areas of relatively pristine rainforest (Glomsrød et al 1997;Horgan 1999). During this period, regional meat and dairy production has increased by over 32 and 23% respectively, with strong upward trends in the sizes of all national herds (Secretaria de Integración Económica Centroamericana 2002).…”
Section: Introductionmentioning
confidence: 99%